Enhancing Infrastructure Development: The Role of Geophysical Methods in Civil Engineering Projects - Sarjan, Achmad Fajar Narotama; Muchtaranda, Ismail Hoesein (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Geophysical engineering and civil engineering are related fields that are essential to the planning, building, and sustainability of infrastructure projects. Geophysical methods provide essential insights into subsurface conditions, enabling civil engineers to optimize infrastructure design, ensure long-term safety, and mitigate risks. The integration of geophysical techniques into civil engineering has transformed project workflows by offering non-invasive solutions for subsurface investigations, reducing the reliance on intrusive methods such as drilling and others that are disruptive to the environment. These methods are particularly valuable in high-cost infrastructure projects, such as bridges, tunnels, and dams, where understanding the subsurface is crucial for structural integrity. This study, based on a comprehensive literature review, analyzes the capabilities and applications of geophysical methods, including ground penetration radar, seismic method, and electrical resistivity in civil infrastructure projects. This study outlines the current state of knowledge and identifies potential to improve the use of geophysical techniques in civil infrastructure projects by combining findings from prior research.